Automated robotic-assisted patient positioning method and dosimetric impact analysis for boron neutron capture therapy - Jiang Chen; Yi-Chiao Teng; Diyun Shu; Qiuping Gong; Qiaolin Xie; Yuan-Hao Liu (Scientific Reports)
Abstract Boron Neutron Capture Therapy (BNCT) represents a revolutionary approach in targeted radiation treatment for cancer. While the therapy’s potential in precise targeting is well-recognized, a critical bottleneck remains in the accurate positioning of patients for treatment delivery. This study proposes a novel automated robotic-assisted patient positioning system specifically engineered for BNCT applications. The system utilizes high-precision industrial robotics and is fully integrated with NeuMANTA, a proprietary treatment planning system designed for BNCT. Through a systematic workflow, the robotic arm algorithmically calculates and executes the patient’s positioning based on the treatment plan, thus enhancing the accuracy and efficacy of the treatment. We validate the positioning system using an anthropomorphic phantom and evaluate the dosimetric impact of positional deviations. The results indicate that the system achieves high accuracy, with a maximum observational deviation of 3 mm in Source-to-Skin Distance (SSD) and 2 mm along the surface. Dosimetric analysis reveals that the resulting dose changes are less than 1% in surface orientation deviations and less than 5% in SSD orientation deviations. The study concludes that the robotic patient positioning system substantially advances in BNCT treatment delivery. This work not only sets a new benchmark for patient positioning in BNCT, but also provides a comprehensive framework for integrating advanced robotics into radiotherapy, paving the way for more precise and effective cancer treatments.